Dogs - Alderton, David, 1956- (Smithsonian handbooks., 2022)
"Authoritative text, crystal-clear photography, and a systematic approach make this the most comprehensive and concise pocket guide to dogs of the world. Packed with more than 1,000 full-color photographs of over 300 dog breeds, this handy reference book is designed to cut through the process of identification and help you to recognize a breed quickly and easily. Expertly written and thoroughly vetted, each entry combines a precise description with annotated photographs to highlight the characteristics and distinguishing features of each breed, while bands provide at-a-glance facts for quick reference. The introduction traces the evolution of the domestic dog, explains the difference between pedigrees and non-pedigrees, looks at how breeds are classified, and examines their characteristics in detail" --